Respostas
respondido por:
2
X= -b +-√b²-4ac ÷ 2a
X= -1 +-√1²-4 ·1 · (-6) ÷2 · 1
X= -1 +-√1+24 ÷2
X= -1 +-√25 ÷ 2
X= -1+- 5 ÷2
X¹= -1 + 5 ÷2
X¹= 4÷2
X¹= 2
X²= -1-5 ÷2
X²= -6÷2
X²= -3
Os zeros da função são 2 e -3
X= -1 +-√1²-4 ·1 · (-6) ÷2 · 1
X= -1 +-√1+24 ÷2
X= -1 +-√25 ÷ 2
X= -1+- 5 ÷2
X¹= -1 + 5 ÷2
X¹= 4÷2
X¹= 2
X²= -1-5 ÷2
X²= -6÷2
X²= -3
Os zeros da função são 2 e -3
respondido por:
1
Explicação passo-a-passo:
Os zeros dessa função são
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás